Keanekaragaman Burung di Sungai Mamberamo, Papua (Short Communication) - Freddy Pattiselanno (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
TheMamberamo-Rouffaer-IdenburghRiverwatershed, one of the wetland sites inWest Papuais the largest tropical marshlands in northern Papua, covers 7,711,602 hectares and includes in the North Papuan Lowlands Endemic Bird Area (EBA). The Irian Jaya Biodiversity Conservation Priority-Setting Workshop (Conservation International, 1999) highlighted that theMamberamoBasinis an area with high priority for conservation. It is also acknowledged little biological information has been collected therefore it is urgent to carry out biological and ecological study in this particular sites.